BLACK SEA STORM RISK FACTOR FOR THE CRITICAL INFRASTRUCTURE OF THE ROMANIAN COASTAL SPACE - Georgeta BANDOC (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2010)
Romanian coastal environment is affected, as clearly appears in the analysis of phenomena regions risk map of Romania, by two distinct categories of natural hazards namely climate risks (mainly storms) and the risks arising from changes in sea level. Climate risks act on short and very short term, resulting in acceleration of all coastal and beach processes, causing profound morphological changes on ecosystems and property damage by inducing destruction of facilities, port construction, settlements, etc. Risks caused by changing sea levels have long-term effect, current growth rates causing damage in the coming 25 ... 50 years. Combined, these two categories of natural hazards adversely induce higher proportion of critical infrastructure in the Romanian coastal area.